Limited impact of several years of pretreated wastewater discharge on fauna and vegetation in a mangrove ecosystem. Issue 1 (April 2018) - Capdeville, C.; Abdallah, K.; Buffan-Dubau, E.; Lin, C.; Azemar, F.; Lambs, L.; Fromard, F.; Rols, J.L.; Leflaive, J.
Abstract: It was hypothesized that mangroves, tropical wetlands, could be used for the finishing treatment of domestic wastewaters. Our aim was to determine if a nutrient-stressed mangrove could tolerate long-term discharges of pretreated wastewater (PW). Since 2008, in an in situ experimental system set up in Mayotte Island (Indian Ocean), domestic PW are discharged into two impacted areas (675 m 2 ) dominated by different species of mangrove trees. Anthropogenic inputs during > 4.5 years led to an increase in vegetation growth associated with an increase in leaf pigment content, leaf surface and tree productivity. A marked increase in tree mortality was observed. There was no effect on crabs and meiofauna densities, but significant modifications of community structures. These effects may be directly linked to PW inputs, or indirectly to the modifications of the environment associated with higher tree growth. However, our results indicate that there was no major dysfunction the ecosystem. Graphical abstract: Highlights: Mangrove forests were proposed as receptacle for domestic wastewaters. The long-term responses of mangrove used for 4.5–6.5 years were studied in situ . Freshwater and nutrient inputs induced a significant increase of vegetation growth. Crab and meiofauna community structures were modified with no decrease of density. No major dysfunction of the ecosystem was observed after long-term anthropic input.